More Machiavelli in Brussels : the art of lobbying the EU - Schendelen, M. P. C. M. van, 1944- (Amsterdam University Press, 2010)
Countless interest groups representing governments and non-governmental bodies try to lobby the European Union effectively in pursuit of the desired legislation, subsidies and more. Many lobby groups simply do what they see fit. Others manage their affairs in the EU arena more professionally, and it is their home front and their playing field which are the focus of this book. Filled with real cases, examples of good practice, and special issues of EU lobbying, it presents a wealth of information and analysis. Like other political processes, EU lobbying has its limits, acknowledged here, alongside its contribution to democracy, both of which are discussed in this thought-provoking and reflective book.